Effects Of Transient Aerodynamics On Vehicle Stability: A Large Eddy Simulation Analysis - Cheng, See Yuan; Tsubokura, Makoto; Nakashima, Takuji; Okada, Yoshihiro; Nouzawa, Takahide (2012)
The present study investigated the extent to which the results obtained from simple bluff body model, regarding pitching stability, can be applied to real vehicle aerodynamics. The investigation was carried out using a large eddy simulation method with vehicle-motion-airflow dynamic coupling capability. The aerodynamic damping coefficient and mechanism obtained from realistic sedan-type vehicle model cases are found similar to the one for simple body model cases. These agreements deduce that the use of simple body model in automotive aerodynamic research is justifiable.